The Development of Mathematics Learning Instructional Model Based on Constructivist Theory to Enhance Analytical Thinking Skills for Grade 8 Students’ Learning about Introduction to Real Numbers - Suwannasri, Penpak (Journal of Teacher Professional Learning Community (JTPLC) (Online), 2023)
This research aimed to develop and implement the mathematics learning instructional model based on constructivist theory to enhance analytical thinking skills for Grade 8 students’ learning about introduction to real numbers. Target group was Grade 8 students in Banlanwittayakom school. The findings revealed that the learning model is called PIACA model. This model consists of 5 stages of teaching including 1) Preparation, 2) Introduction, 3) Analysis, 4) Construction, and 5) Application. The learning model had efficiency of implementing in 85.45/86.90. Post test of students’ achievement was significantly (.05) higher than pretest. Approximately ninety percents of students held scores of students’ analytical thinking skills higher than eighty percent. And students held satisfactory toward the implementation of PIACA in very good level.